Effect of membrane material and pore size on membrane fouling during filtration of algae-laden water - Shan-shan Gao; Xin-hong Zhang; Ming-yue Geng; Jia-yu Tian (Water Science and Engineering)
Membrane filtration technology has been widely utilized for microalgae harvesting due to its stability and high efficiency. However, this technology faces challenges posed by membrane fouling caused by algal cells and extracellular organic matter (EOM), which are significantly influenced by membrane material and pore size. This study compared the fouling behavior of polyvinylidene fluoride (PVDF) membranes and ceramic membranes with similar pore sizes (0.20 μm and 0.16 μm, respectively) during the filtration of Microcystis aeruginosa. The ceramic membrane exhibited a lower transmembrane pressure (TMP) growth rate and reduced accumulation of surface foulants compared to the PVDF membrane, indicating its greater suitability for filtering algae-laden water. Further investigations employed membranes fabricated from aluminum oxide powders with grain sizes of 1 μm, 3 μm, 8 μm, and 10 μm, corresponding to membrane pore sizes of 0.08 μm, 0.16 μm, 0.66 μm, and 0.76 μm, respectively, to assess the impact of pore size on ceramic membrane fouling. The results revealed that increasing membrane pore size significantly lowered the TMP growth rate and reduced the irreversibility of membrane fouling. The extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) analysis indicated that large pore sizes enhanced repulsion between the ceramic membrane and algal foulants, further alleviating membrane fouling. This investigation offers new insights into optimizing membrane material and pore size for efficient filtration of algae-laden water.